Acute toxicity study of cosmos caudatus on Biochemical Parameters in Male Rats - M. Norazlina,; S.Z., Ehsan; K., Noor 'Adilah; C.P., Lee; E., Farhana; P., Derick; S., Ima-Nirwana; A.S., Nazrun; M., Norliza (Universiti Kebangsaan Malaysia, 2013)
Cosmos caudatus or ‘ulam raja’ is a local plant with antioxidant properties and has the potential to treat free radicals-associated diseases. However, its toxic effects need to be elucidated. Acute toxicity study was carried out in male rats. Rats aged 3 months, weighing 150-200 g were divided into 4 groups, i.e. rats being fed on distilled water (control), Cosmos caudatus extract dose 50 mg/kg (CC50), Cosmos caudatus 500 mg/kg (CC500) and Cosmos caudatus 2000 mg/kg (CC2000), respectively. A single treatment was given to the respective groups and the animals were sacrificed after 7 days. Biochemical parameters before and after treatment were measured. Liver enzymes, i.e. alkaline phosphatase (ALP) and alanine transaminase (ALT), were found to be increased post treatment in CC500 and CC2000 groups. Creatinine levels were lower in CC500 and CC2000 groups post treatment compared with control group while albumin levels were lower in CC2000 group than all the other groups. In conclusion, Cosmos caudatus may cause acute hepatotoxicity at high doses.